THE HISTORICITY OF CLASSIC ORIENTALISM, ISLAMOLOGY AND SCRIPTURE TRANSLATION (A NEW ANALYSIS) - Huda, Moh. (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2021)
This study aims to determine the history of the development of orientalism in the classical era and the mission of translating the Qur'an and Islamic studies. This is based on the author's concern that the model of Islamic studies and the study of the Koran in the contemporary era is still rigid from an interdisciplinary study. This study is a library research study with data exposure using descriptive and analytical-critical methods. The findings in this study indicate that classical orientalism has led to attempts to confront Islamic thoughts. One of the fruits of this conflict was the presence of a translation of the al-Qur'an, the work of the orientalists. However, this competitive contestation eventually gave rise to an interdisciplinary model of Islamology and the study of the Al-Qur’an.